Cross-sectional assessment of three commonly used measures of adherence to combination antiviral therapy in a resource limited setting. (January 2017) - Luma, Henry N; Mbatchou Ngahane, Bertrand H; Mapoure, Yacouba N; Mengjo, Neville B; Temfack, Elvis; Joko, Henry A; Asongalem, Emmanuel A; Koulla-Shiro, Sinata
Nowadays, global coverage of combination antiretroviral therapy (cART) has increased due to a continuous process to scale up access. This increase has potentially transformed HIV-infection from a fatal to a chronic disease: a transformation only possible if the prescribed medications are taken accordingly. We therefore evaluated optimal adherence to cART by three commonly used methods: visual analogue scale (VAS), four days recall (FDR) and clinic attendance (CA) for the last six months in 301 HIV-infected patients on cART for at least six months at the Douala General Hospital, Cameroon. Optimal adherence was defined to be greater than or equal to the 95th percentile estimate of each method. We found that 70.8% of our study population was female. The mean age was 40.8 years (SD 10.5) and 85% were on first line cART. Median CD4 count was 397 cells/ml (252–559). Optimal adherence by VAS, FDR and CA, was 68.1%, 83.4%, and 73.4%, respectively. VAS and FDR inter-correlated strongly (Pearson's Chi square coefficient, r = 0.58, p  < 0.001). Higher CD4 count above 200 cells/ml was associated with optimal adherence by CA (Adjusted Odds Ratio [AOR]:2.6 (95% CI: 1.2–5.3, p  < 0.001)). As high optimal adherence to cART is associated with good clinical outcome in HIV patients, simple methods such as the VAS for evaluating adherence, should be integrated to the HIV clinic of the Douala General Hospital.